The incidence of VP shunt infection in a middle-income nation: a retrospective analysis of a pediatric population - Campbell, Dwayne; Sinclair, Shane; Cooke, Dwaine; Webster, Dwight; Reid, Marvin (Frontiers in Surgery, 2023)
To investigate the incidence of infection Post Ventriculoperitoneal shunt insertion at the Bustamante Hospital for Children (BHC), Jamaica.One hundred and seventy-eight (178) patients being managed by the Neurosurgery team, underwent surgery during the period of 2010 -2016 at BHC. One hundred and twenty-two went on to have Cerebrospinal Fluid (CSF) diversion via a Ventriculoperitoneal Shunt (VPS) placement. Patients were excluded if the VPS was placed at another institution or prior to the period. There is a noted transition that saw the switch from Codman uniport to Medtronic shunts in 2014-2015 and the led to the start of the re-using of shunt passers. Clinical data were retrospectively collected from operating theatre logs and manual health records available.Over the 7-year study period of the 122 first time shunt placement done, a total 17 (13.9%) had positive CSF cultures with an additional 6 (4%) having CSF pleocytosis with negative cultures. The most common isolate being of the Staphylococcus species, occurring in 60% VPS infection. The median time to shunt infection was 2 months. 6 of the 72 Codman shunts became infected and 21.7% (10 of 46) of Medtronic Shunts became infected.The incidence of VPS infection was 13.9% for the period of 2010-2016, with most infection occurring post 2014. The major causative agent was Staphylococcus species at 60% within 2 months of surgery on median. Overall, this compares well with data reported in the literature.